Benefit losses loom larger than taxes: The effects of framing and loss aversion on behavioural responses to taxes and benefits - Silvia Avram (University of Essex, Institute for Social and Economic Research (ISER), 2015)
A substantive body of research highlights the existence of framing effects in labour supply responses to taxation challenging traditional models that assume taxes only influence behaviour via the budget constraint. Using a lab experiment, this paper examines the presence of differential responses to identical marginal tax schedules coming from direct taxation and from benefit withdrawal respectively. In an incentivised real-effort task, subjects supply time and effort while facing an incentive structure that is framed as taxation or benefit withdrawal respectively, while yielding the exact same budget constraint. Results indicate that subjects in the benefit withdrawal condition are more likely to reduce working time compared to both subjects in the tax treatment and a control group where the incentive structure is described without using the language of taxes and benefits. The effect is driven by loss-averse individuals suggesting that benefit streams may be subject to an 'endowment effect'. The findings have clear implications for welfare policy design.
Keywords: C91; D80; I38; 330; framing effects; behavioural responses to taxation; loss-aversion; experiments